How can African agriculture adapt to climate change? Insights from Ethiopia and South Africa - Ringler, Claudia; Shewmake, Sharon; Hassan, Rashid; Admassie, Assefa; Adenew, Berhanu; Tadege, Abebe; Nhemachena, Charles; Deressa, Temesgen T.; Alemu, Tekie; Yesuf, Mahmud; Block, Paul J.; Strzepek, Kenneth M.; et al. (International Food Policy Research Institute, 2011)
This series of IFPRI Research Briefs is based on research supported by the Federal Ministry for Economic Cooperation and Development, Germany, under the project "Food and Water Security under Global Change: Developing Adaptive Capacity with a Focus on Rural Africa," which forms part of the CGIAR Challenge Program on Water and Food. Through collaboration with the Center for Environmental Economics and Policy in Africa, the Ethiopian Development Research Institute, the Ethiopian Economics Association, and the University of Hamburg, the project aims to provide policymakers and stakeholders in Ethiopia and South Africa with tools to better understand and analyze the consequences of global change-in particular climate change-and to form policy decisions that facilitate adaptation in these countries and bey." -- from text